Manfaat Vaksinasi Influenza pada Anak dengan Gangguan Perkembangan Neurologis: Analisis - Gunawan, Kevin; Santoso, Patricia Melissa Alim; Elvira, Junita (Cermin Dunia Kedokteran, 2025)
Children with neurological or neurodevelopmental disorders (NDDs) are at higher risk for severe flu complications due to limited mobility, weaker respiratory muscles, and abnormal muscle tone, which can affect lung secretion function. Although this group is relatively small, children with NDDs account for a significant number of influenza-related hospitalizations and deaths. Annual vaccination is an effective prevention measure and is recommended for all children aged 6 months to 18 years, including those with NDDs. Family members or caregivers in close contact with these children should also receive annual influenza vaccinations. However, there is still limited research on the influenza vaccine in this group, and its effectiveness can vary each year. This article reviews influenza vaccination in general and specifically for children with NDDs.